Biomimetics : bioinspired hierarchical-structured surfaces for sreen science and technology - Bhushan, Bharat (Biological and Medical Physics, Biomedical Engineering, 2012)
This book presents an overview of the general field of biomimetics - lessons from nature. It presents various examples of biomimetics, including roughness-induced superomniphobic surfaces which provide functionality of commercial interest. The major focus in the book is on lotus effect, rose petal effect, shark skin effect, and gecko adhesion.  For each example, the book first presents characterization of an object to understand how a natural object provides functionality, followed by modeling and then fabrication of structures in the lab using nature's route to verify one's understanding of nature and provide guidance for development of optimum structures. Once it is understood how nature does it, examples of fabrication of optimum structures using smart materials and fabrication techniques, are presented. Examples of nature inspired objects are also presented throughout.